Education and development of rehabilitation therapy in China under the background of aging - Sun, Shuyue; Lin, Xingru; Ouyang, Xiaoyao; Cai, Weiqin; Gao, Qianqian; Guo, Peiwu; Li, Zongrun; Ji, Lihong; Dong, Zhiwei; Jing, Qi; Zhang, Jianhua (Frontiers in Public Health, 2022)
The World Health Organization (WHO) estimates that about one-third of people worldwide currently have a need for rehabilitation. This demand is expected to increase in the coming years due to changes in population health and characteristics. For example, with the intensification of global aging, the rehabilitation needs of patients with chronic diseases and disabilities, postoperative dysfunction, and cognitive impairment continue to grow, and emergencies such as conflicts, disasters, and epidemics may lead to a surge in rehabilitation needs. Early and sustained rehabilitation could reduce complications, improve function, and reduce disability in affected populations, but rehabilitation services are often underestimated due to underfunding and poor short-term outcomes. WHO sees rehabilitation as an essential part of achieving universal health coverage and the Sustainable Development Goals. With the development of China's economy and society and the trend of an aging population, the demand for rehabilitation therapists is growing rapidly. Since the development of rehabilitation education in China at the beginning of this century, great progress has been made in both the training mode and the number of people trained, especially in the construction of higher education of rehabilitation in related colleges and universities. Through descriptive qualitative analysis, this study collected information from national policy documents and official websites of colleges and universities on policies concerning degree systems, cultivating goals and ideas, courses, education internationalization, continuing education in practice, standardized training after graduation, the number of colleges and universities with rehabilitation therapy related majors in China, and summarizes the current situation of the development of rehabilitation personnel education in Chinese colleges and universities. Judging from the results, during the development of rehabilitation education, China has continuously improved in terms of policy support, educational goals and concepts, the number and quality of institutions, degree systems, and internationalization, while gradually adapting to China's development status. This also provides direction and feasible suggestions for China to improve the rehabilitation education development system and formulate a national rehabilitation education plan in the future to deal with the challenge of aging.